PENGUMUMAN ONLINE DENGAN NOTIFICATION SYSTEM DAN PENCARIAN INFORMASI MENGGUNAKAN METODE TF-IDF - Chintia Yusnita Violetta; Lely Hiryanto; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Application Announcement Online with Search Information Notification System and method TF-IDF is an application that uses the notification system on email, facebook group, twitter to help convey information related to teaching and learning in the Faculty of Information Technology University Tarumanagara. In addition, there is information search function to find information relevant to a query by using the TF-IDF algorithm. Based on test results, notifications on email, facebook group, twitter managed to send the announcement via their respective social media. Testing information search data can also provide information relevant results to the query. Key WordsNotification System, Online Announcement, TF-IDF.